In vitro and in vivo Antidiabetic Properties of Phenolic Antioxidants From Sedum adenotrichum - Naz, Dil; Muhamad, Ali; Zeb, Alam; Shah, Ismail (Frontiers in Nutrition, 2019)
Natural products serve as the mainstay of human life and today almost half of the drugs in clinical practice are the natural origin. Keeping in view the importance of medicinal plants and natural products, Sedum adenotrichum also known as Rosularia adenotrichum was selected for the present study. The crude extract of Sedum adenotrichum whole plant was obtained through a rotary evaporator. The extract was analyzed for a polyphenolic profile using HPLC-DAD. The extract was subjected to detail in-vivo anti-diabetic study. In this study, body weight, blood glucose level, glycated haemoglobin, lipid profile, liver function tests and renal function tests were performed in animal models. The extract was tested for in-vitro α-glucosidase inhibition activity. Results of HPLC-DAD chromatogram revealed a total of 22 polyphenolic compounds. No major change in body weight was noted in experimental animals. Alloxan induction led to a significant elevation in plasma glucose level. A significant decline was noted in blood glucose & glycated haemoglobin concentration in rats treated with the extract as well as with glibenclamide. Renal/liver function tests, lipid profile, ALP and serum cholesterol were normalized by the extract-treated rats. The α- glucosidase inhibitory activity at 62.5 and 1000 µg/ml was noted to be 63.97 and 80.80, respectively, both approaching to standard. The results reveal that the extract was rich in important phenolic compounds. In the anti-diabetic potentials of the crude extract, there might be involved several pancreatic and extra-pancreatic mechanisms acting synergistically to induce the potent anti-diabetic effect.